Curiosity as an approach to ethoexperimental analysis: behavioral neuroscience as seen by students and colleagues of Bob Blanchard - Pearson, Brandon L. (Neurosci Biobehav Rev, 2016)
This review is a synopsis of an IBNS symposium which focused on the elements of Behavioral Neuroscience for which Robert J. Blanchard was a Pioneer, Leading Expert, Advocate, Mentor, and Sage. Bob Blanchard’s work demonstrably changed our broad understanding of animal behavior, and led the way to experimental design and analysis for studies of animal behavior that helped to clarify the deep complexity and subtleties of behavior. Bob’s impact on the field of Behavioral Neuroscience includes the behavior, neurocircuitry, neurochemistry, and pharmacology related to social interactions, aggressive behavior, defensive behaviors, flight, freezing, threat, attack, risk assessment, anxiety disorders, animal models, models of social behavior, and autism. The methods and designs developed by Bob Blanchard over a lifetime have been adopted by scientists around the world, and form a standard of excellence in the field. The article addresses these topics in a way that presents developments in the field, describes the newest research data, and pays tribute to a great scientist and founder of this field of work, Bob Blanchard.